(untitled) (Communications in Computational Physics, 2026)
In [J. Wang, G. Hu, arxiv: 2302.14262], a dual-consistent dual-weighted residual-based h-adaptive method has been proposed based on a Newton-GMG framework, toward the accurate calculation of a given quantity of interest from Euler equations. The performance of such a numerical method is satisfactory, i.e., the stable convergence of the quantity of interest can be observed. In this paper, we will focus on the efficiency issue to further develop this method. Three approaches are studied for addressing the efficiency issue, i.e., i). using convolutional neural networks as a solver for dual equations, ii). designing an automatic adjustment strategy for the tolerance in the h-adaptive process to conduct the local refinement and/or coarsening of mesh grids, and iii). introducing OpenMP, a shared memory parallelization technique, to accelerate the module such as the solution reconstruction in the method. The feasibility of each approach and numerical issues are discussed in depth, and significant acceleration from those approaches in simulations can be observed clearly from a number of numerical experiments. In convolutional neural networks, it is worth mentioning that the dual consistency plays an important role in guaranteeing the efficiency of the whole method and that unstructured meshes are employed in all simulations.